2019
DOI: 10.1007/s10198-019-01058-x
|View full text |Cite
|
Sign up to set email alerts
|

The burden of informal caregiving in Hungary, Poland and Slovenia: results from national representative surveys

Abstract: Background We aimed to investigate the burden of informal care in Hungary (HU), Poland (PL) and Slovenia (SI). Methods A cross-sectional online survey was performed involving representative samples of 1000 respondents per country. Caregiving situations were explored; health status of informal caregivers/care recipients and care-related quality of life were assessed using the EQ-5D-5L and CarerQol-7D. Results The proportion of caregivers was (HU/PL/SI) 14.9, 15.0 and 9.6%, respectively. Their mean age was 56.1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
28
1
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 30 publications
6
28
1
7
Order By: Relevance
“…The current study nds that the females with high educational attainment are more likely to play the role of be high-intensity caregivers, while this education effect is not found to be statistically signi cant in lowintensity informal caregivers. This nding is in agreement with the conclusion of Petra et al that high education was associated with a higher probability of being a caregiver in Poland, though they did not particularly focus on females [21]. One important reason for this nding might be due to the "feedback theory" proposed by Xiaotong Fei [41].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The current study nds that the females with high educational attainment are more likely to play the role of be high-intensity caregivers, while this education effect is not found to be statistically signi cant in lowintensity informal caregivers. This nding is in agreement with the conclusion of Petra et al that high education was associated with a higher probability of being a caregiver in Poland, though they did not particularly focus on females [21]. One important reason for this nding might be due to the "feedback theory" proposed by Xiaotong Fei [41].…”
Section: Discussionsupporting
confidence: 90%
“…This thus, the women with higher SES have a greater capacity to purchase formal institutional care for their older parents instead of informal care in the above mentioned high-income counties. Although the study in Poland is consistent with our ndings [21], it may be due to its lack of a public insurance fund for long-term care for older people. By contrast, in China and many other LMICs, the long-term care system is still in its infancy, and informal care remains the dominant.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Providing informal care can lead to mental health problems such as stress, fear, depression, and concerns about the future and the caregiving tasks. 23 Studies have demonstrated that, over time, as the elders dependence on care increases, the difficulties of taking care of another person may create burden and feelings of stress, and may contribute to caregiver depression, affecting their quality of life. 24,25 The study was limited by the small sample size, precluding the generalization of results to the general population.…”
Section: Discussionmentioning
confidence: 99%
“…SES was found to be a key determinant of the amount of caregiving, including informal and formal care, which was mainly due to accessibility, awareness, and ,affordability. [9] A study found that there was a positive association between informal caregiving intensity and income among the White caregivers in the United states. [10] Another study conducted in the United States indicated that many low-income households were unable to afford formal care services.…”
Section: Introductionmentioning
confidence: 99%